Characterization of the Silante Fm. Along the Salinas-Lita Transect in Northern Ecuador - Sarmiento López, Luis Bryan (2020)
The Silante formation is a sequence of strata deposited in a continental environment that spans around 100 km which extends in a belt from the Ilinizas in the south to the Salinas-Lita transect in the north. It is composed of breccias, matrix supported conglomerates, red mudstone, siltstone and tuff. The Silante Formation has been described very well at west of Quito, in the Aloag-Santo Domingo transect and the Calacali-Nanegalito transect. However, it has not been studied in detail at the northern end of the Silante belt, along the Salinas-Lita transect. For this reason, we focused on this location. This study consisted mostly of field surveys which were: geological mapping of the work area, sedimentological and petrographic description of the strata, and the measurement of deformation features. As a result, we divided Silante Fm into two members, we describe changes in deposition environments, and we identify an important phase of deformation of the WC.